EMG-driven computer game for post-stroke rehabilitation - Xing Shusong; Zhang Xia (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
The key point of post-stroke rehabilitation is that exercices and therapy must begin as soon as possible after stroke in order to let the survivors regain their body movement functions. By playing the EMG-driven computer game, the patients can locate disused body parts and start training their muscles even when they have to stay on beds during the early stage of rehabilitation. Wearable EMG nodes for post-stoke rehabilitation are made in affordable price and a toy robot controlled by the computer game is used to communicate with the people.